2016
DOI: 10.1080/02626667.2014.987675
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of four high-resolution satellite precipitation products under diverse climate conditions in Iran

Abstract: High-resolution satellite-retrieved precipitation products are useful input data for hydrologic predictions and water resources management, especially in developing countries where the availability of ground-based rainfall measurements with high spatial coverage is very limited. In this study, four widely used satellite rainfall estimates (TMPA-3B42V7, TMPA-3B42RT, PERSIANN, and CMORPH) are evaluated with a dense raingauge network over six regions with various physiographic and climate conditions in Iran. Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 29 publications
6
39
0
Order By: Relevance
“…Additionally, the GPM constellation satellites' product (IMERG) was superior to the TRMM Multi-satellite Precipitation Satellites (TMPA) product (3B42). Moreover, all three satellite/model products underestimated the precipitation in this region, a similar conclusion by Moazzami et al [13] and Javanmard et al [11] who tested 3B42 in this region. Such findings may be attributed to local wind and convective precipitation in this region so that satellites could not detect precipitation properly.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Additionally, the GPM constellation satellites' product (IMERG) was superior to the TRMM Multi-satellite Precipitation Satellites (TMPA) product (3B42). Moreover, all three satellite/model products underestimated the precipitation in this region, a similar conclusion by Moazzami et al [13] and Javanmard et al [11] who tested 3B42 in this region. Such findings may be attributed to local wind and convective precipitation in this region so that satellites could not detect precipitation properly.…”
Section: Discussionsupporting
confidence: 66%
“…Another tool to determine precipitation at relatively fine temporal and spatial scale is satellite observation. During the last decade, many researchers have evaluated and used satellite data sets and some have found that the TMPA-3B42 post real-time product performed better than other products compared with the rain-gauges [9][10][11][12][13][14][15]. One of the disadvantages of TMPA-3B42 was the limited area of observation; it covered only the tropical and subtropical belts.…”
Section: Introductionmentioning
confidence: 99%
“…However, Moazami et al . () focused on a comprehensive evaluation of four satellite rainfall estimates over Iran, including PERSIANN, TMPA‐3B42‐V7, TMPA‐3B42RT and CMORPH. Their results show that in most cases the underestimation of rainfall is quite large at high rainfall ranges.…”
Section: Introductionmentioning
confidence: 97%
“…A number of different evaluations of satellite rainfall estimates have previously been carried out over Iran (e.g. Javanmard et al, 2010;Katiraie-Boroujerdy et al, 2013;Moazami et al, 2016;Alijanian et al, 2017). The evaluation of different satellite rainfall estimates reveals that the results vary in different areas (Katiraie-Boroujerdy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation